Improvement of recycled paper's properties for the production of braille paper by impregnation with low grade cellulose acetate: Optimization using response surface methodology (RSM) - Mei Chong Soo; Wan Rosli Wan Daud; Cheu Peng Leh (BioResources, 2012)
Paper dust is a kind of cellulosic waste that is generated by converting operations in paper mills. It was derived to a low-grade cellulose acetate in this study. Papers made from recycled fiber were then impregnated with the resultant cellulose acetate. Effects of impregnation conditions on the paper properties were statistically investigated by employing central composite design (CCD) based response surface methodology (RSM). Four response variables, namely density, burst index, smoothness, and rate of surface wettability were analyzed. Polynomial estimation model of each response was developed as functions of three independent variables, which are pressing temperature (T), dipping time (D), and concentration of cellulose acetate (C). The paper which was impregnated based on the calculated optimum condition (T: 163 oC, D: 2.8 minutes, and C: 2.7 percent), possessed a density of 0.5450 g/cm3, rate of surface wettability of 0.012o/s, burst index of 2.84 kPa m2/g, and paper smoothness of 475 mL/min. There was no significant difference between the experimental values and the predicted values calculated from estimation models. The cellulose acetate impregnated Braille papers made from recycled fibre was found to have better properties than those of commercial Braille paper in terms of rate of surface wettability and burst index.